2021
DOI: 10.1186/s40729-021-00386-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of inflammatory peri-implant diseases using an immunochromatographic assay for calprotectin in peri-implant crevicular fluid

Abstract: Background The incidence rate of peri-implant diseases is increasing with implant placement. Early detection of peri-implant diseases is important to prevent and treat these diseases, and a simple and objective diagnostic method is expected. Immunochromatographic (IC) assays are used for rapid diagnostic methods for some diseases. The aim of this clinical study was to determine the amount of calprotectin, an inflammatory marker, in peri-implant crevicular fluid (PICF) using an IC chip, and esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…A deeper knowledge of the inflammatory mechanisms, protein biomarkers, and cytokines involved in peri‐implant disease progression could be crucial for clinicians, since this can guide the early treatment through nonsurgical methods (e.g., immunomodulators and cytokine inhibitors) and surgical preventive approaches that may improve the stability of peri‐implant soft tissue structures that protect the subsequent peri‐implant crestal bone. Several studies evidenced that biomarkers for IL‐1ß, IL‐ 6, IL‐17, matrix metalloproteinases, VEGF, TNF‐α, and adipokines are significantly higher at peri‐implant diseased sites' crevicular fluid samples when compared to healthy samples 11,21,26–29 . Remarkably, certain studies have pointed that those pro‐inflammatory biomarkers are associated to thin PSP features presenting inadequate keratinized mucosa (KM) width, reduction of mucosal attachment, and higher marginal recession levels 20,21 .…”
Section: Inflammatory Mechanisms and Disease Progression At The Soft ...mentioning
confidence: 99%
See 1 more Smart Citation
“…A deeper knowledge of the inflammatory mechanisms, protein biomarkers, and cytokines involved in peri‐implant disease progression could be crucial for clinicians, since this can guide the early treatment through nonsurgical methods (e.g., immunomodulators and cytokine inhibitors) and surgical preventive approaches that may improve the stability of peri‐implant soft tissue structures that protect the subsequent peri‐implant crestal bone. Several studies evidenced that biomarkers for IL‐1ß, IL‐ 6, IL‐17, matrix metalloproteinases, VEGF, TNF‐α, and adipokines are significantly higher at peri‐implant diseased sites' crevicular fluid samples when compared to healthy samples 11,21,26–29 . Remarkably, certain studies have pointed that those pro‐inflammatory biomarkers are associated to thin PSP features presenting inadequate keratinized mucosa (KM) width, reduction of mucosal attachment, and higher marginal recession levels 20,21 .…”
Section: Inflammatory Mechanisms and Disease Progression At The Soft ...mentioning
confidence: 99%
“…Several studies evidenced that biomarkers for IL-1ß, IL-6, IL-17, matrix metalloproteinases, VEGF, TNF-α, and adipokines are significantly higher at peri-implant diseased sites' crevicular fluid samples when compared to healthy samples. 11,21,[26][27][28][29] Remarkably, certain studies have pointed that those proinflammatory biomarkers are associated to thin PSP features presenting inadequate keratinized mucosa (KM) width, reduction of mucosal attachment, and higher marginal recession levels. 20,21 Moreover, some studies have also evidenced that the pro-inflammatory biomarker expression at peri-implant diseased sites was significantly reduced by antibacterial and anti-inflammatory therapies and also after soft tissue grafting techniques that improved the PSP.…”
Section: Inflammatory Protein Biomarkersmentioning
confidence: 99%
“…44 These factors are the biomarkers of peri-implant inflammatory conditions. 45,46 Therefore, a high level of patient motivation, the foundation for their willingness to undergo periodic intraoral follow-up evaluations, is another requirement for long-term implant survival. Frontal linear scleroderma "en coup de sabre" in a female patient was described by Zanettini et al 31 Their findings suggest that oral reconstruction could be accomplished.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblasts’ activities can also be endorsed through enhancement in Wnt signaling, which can cause diverse bone affections as typically observed in the disease 44 . These factors are the biomarkers of peri‐implant inflammatory conditions 45,46 . Therefore, a high level of patient motivation, the foundation for their willingness to undergo periodic intraoral follow‐up evaluations, is another requirement for long‐term implant survival.…”
Section: Discussionmentioning
confidence: 99%
“…A significant correlation was also reported by them between calprotectin IC reader value and PD. They found that BOP-positive sites had much higher levels of calprotectin than BOP-negative sites [ 27 ].…”
Section: Discussionmentioning
confidence: 99%